2015
DOI: 10.3109/02770903.2015.1054404
|View full text |Cite
|
Sign up to set email alerts
|

Residual exhaled nitric oxide elevation in asthmatics is associated with eosinophilic chronic rhinosinusitis

Abstract: FeNO levels were elevated even in well-controlled asthmatics with ECRS, whereas asthmatics without ECRS and ECRS patients without asthma did not have high FeNO levels (>50 ppb). Although FeNO levels were not correlated with asthma severity, they were positively correlated with the sinus CT score. In asthmatics with ECRS, patients with higher FeNO levels had more severe ECRS and asthma. There is a possibility of having comorbid ECRS, particularly in asthmatics with high FeNO levels even after adequate treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Likewise, ECRS, similar to AR, contributes to T helper 2 (Th2)-skewed pathology and is strongly associated with severe asthma [11,13]. Indeed, we have reported that fractionated exhaled nitric oxide reflective of disturbance of lung function was correlated with sinus computed tomography (CT) score based on the Lund–Mackay scale [16].…”
Section: Etiology Of United Airway Diseasementioning
confidence: 99%
“…Likewise, ECRS, similar to AR, contributes to T helper 2 (Th2)-skewed pathology and is strongly associated with severe asthma [11,13]. Indeed, we have reported that fractionated exhaled nitric oxide reflective of disturbance of lung function was correlated with sinus computed tomography (CT) score based on the Lund–Mackay scale [16].…”
Section: Etiology Of United Airway Diseasementioning
confidence: 99%
“…Approximately half of the patients with ECRS have bronchial asthma ( 3 ), which is a risk factor of relapse after endoscopic sinus surgery ( 4 ). Furthermore, in those with severe ECRS, asthma is significantly associated with ECRS in more than 80% of cases ( 4 , 5 ). Conversely, a recent report suggests that more than 50% of patients with severe asthma also had ECRS ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of comorbid asthma and ESS on type 2-driven inflammation in CRS patients have been reported by using blood eosinophil, serum periostin, and FeNO [20, 24-26, 37, 39-41]. Serum periostin levels are significantly increased in asthmatics by having comorbid CRS [20, 24, 25], along with blood eosinophils [26] and FeNO [25, 26, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Serum periostin levels are significantly increased in asthmatics by having comorbid CRS [20, 24, 25], along with blood eosinophils [26] and FeNO [25, 26, 40]. Also, increased FeNO levels were correlated with radiological CRS severity in ECRS patients [37, 39]. We have already demonstrated that blood eosinophils, serum periostin, and FeNO are applicable for use in distinguishing comorbid CRS among patients with asthma [25].…”
Section: Discussionmentioning
confidence: 99%